Municipal solid waste landfill: Evidence of the effect of applied landfill management on vegetation composition - Vaverková, Magdalena Daria; Paleologos, Evan K; Adamcová, Dana; Podlasek, Anna; Pasternak, Grzegorz; Červenková, Jana; Skutnik, Zdzisław; Koda, Eugeniusz; Winkler, Jan (Waste management & research, 2022)
Proper management of municipal solid waste (MSW) is crucial to avoid pollution, environmental impacts and threat to public health. The problem of MSW is mainly arising from inadequate landfill site management. The objective of this study was to evaluate the impact of management practices and environmental risks at two landfill sites. The landfills were subject to long-term (10 years) vegetation monitoring. The vegetation was assessed using a floristic survey of identified plant species. The vegetation analysis showed that significant differences existed between the two landfill locations, with neophytes, invasive and expansive species dominating on one of the landfill sites, which may be attributed to climatic and geomorphological differences between the two sites, but also to variations in landfill management. These environmentally problematic species can potentially spread from the landfill into adjacent ecosystems, displace native plants and degrade adjacent farmland areas. The study of vegetation monitoring data suggests that, in addition to other types of monitoring, landfills should be subjected to regular vegetation biomonitoring, too. Landfill management practices should target the regulation of unwanted species, create conditions that are favourable to native plant species and provide as early as possible the restoration of filled cells.